2009
DOI: 10.1007/s10342-009-0299-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in the growing stock of trees in Finland under different cutting and climate scenarios

Abstract: In this work the aim was to determine how carbon sequestration in the growing stock of trees in Finland is dependent on the forest management and increased production potential due to climate change. This was analysed for the period 2003-2053 using forest inventory data and the forestry model MELA. Four combinations of two climate change and two management scenarios were studied: current (CU) and gradually warming (CC) climate and forest management strategies corresponding to diVerent rates of utilisation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 53 publications
3
29
1
1
Order By: Relevance
“…These results are consistent with those of Mund and Schulze (2006), who reported that the total amount of carbon in the system decreased as management intensity increased in Fagus sylvatica stands in Germany. The same effect was reported by Matala et al (2009) who observed that future evolution of C in the growing stock depends on forest management, as well as on climate-change scenarios. Moreover, BS increased with site quality for all species studied.…”
Section: Mitigation Effect Of Several Management Alternativessupporting
confidence: 67%
“…These results are consistent with those of Mund and Schulze (2006), who reported that the total amount of carbon in the system decreased as management intensity increased in Fagus sylvatica stands in Germany. The same effect was reported by Matala et al (2009) who observed that future evolution of C in the growing stock depends on forest management, as well as on climate-change scenarios. Moreover, BS increased with site quality for all species studied.…”
Section: Mitigation Effect Of Several Management Alternativessupporting
confidence: 67%
“…Another simulated management strategy, the maximum net present value (NPV) of wood production, resulted in an increase of 18 and 34 %, respectively, compared to the initial growing stock. The results show that future development of carbon sequestration and growing stock is not only dependent on climate change scenarios but on forest management adapting to changing conditions (Matala et al 2009). Similar conclusions were drawn by Köhl et al (2010) for, among others, temperate regions in north-eastern Germany.…”
Section: Adaptive Forest Management Maymentioning
confidence: 99%
“…The highest species-specific opportunity costs (as lost potential benefit) were found for Scots pine (EUR 227 ha −1 ) and the lowest for silver birch (Betula pendula) (EUR 53 ha −1 ). They concluded by stressing the need to adapt future management to utilise the increase in growth under climate change (see also Matala et al 2009). …”
Section: Adaptive Forest Management Maymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the benefits of carbon sequestration by forests have been highlighted and carbon sequestration has been measured throughout the world: in the United States (Sakata 2005;Calish et al 1978;Foley et al 2009;Ehman et al 2002;Im et al 2007), Europe (Backèus et al 2005;Liski et al 2001;Matala et al 2009;Pohjola and Valsta 2007;Sivrikaya et al 2007;Kaipainen et al 2004;Seidl et al 2007), Canada (Hennigar et al 2008;Thompson et al 2009), Oceania (Campbell and Jennings 2004) and Asia (Ravendranath 1995;Han and Youn 2009). Forests not only have economic value through the production of commercial timber, but they also have other values to society including acting as carbon sinks, supporting biodiversity, and providing water protection (Pukkala 2002).…”
Section: Introductionmentioning
confidence: 99%